Protection Of Medical Records In Corona Virus Disease-19 Patients Based On The Law - Lusia Indrastuti (International Journal Of Community Service, 2022)
This study aims to describe the protection of medical records for patients with Covid 19, as it is known that legal protection of patient medical records in general can be seen through various regulatory provisions including Law Number 29 of 2004 concerning Medical Practice, Regulation of the Minister of Health Number 269 of 2008 concerning Medical Records, Law Number 36 of 2009 concerning National Health, this of course provides a variety of perspectives on the protection of medical records which of course has an impact on the existence of the medical record itself, especially if it is associated with the existing conditions of the Covid 19 pandemic. Based on research results It is known that regarding legal protection of patient medical records associated with the Covid 19 Pandemic, the national positive law tends to lack existence and still has various weaknesses, including: a. regulation regarding the permission to open medical records in the case of "public interest" which is still classified as ambiguous or absurd, then b. there are no legal implications of opening or leaking medical records for both doctors and hospitals, in the context of the Covid-19 pandemic, because there is no regulation regarding criminal sanctions in the event that medical records are opened by doctors or hospitals